Antidepressant amitriptyline‐induced matrix metalloproteinase‐9 activation is mediated by Src family tyrosine kinase, which leads to glial cell line‐derived neurotrophic factor mRNA expression in rat astroglial cells - Hiromi Abe; Naoto Kajitani; Mami Okada‐Tsuchioka; Wataru Omori; Masahide Yatsumoto; Minoru Takebayashi (Wiley, 2019)
Abstract Background Astrocytes have been implicated in the pathophysiology of mood disorders and in the mechanism of the pharmacological effects of antidepressant drugs by the production of neurotrophic/growth factors. Previous studies have identified astrocyte‐expressed Gαi/o‐coupled lysophosphatidic acid receptor 1 (LPAR1), as being involved in antidepressant‐induced production of glial cell line‐derived neurotrophic factor (GDNF) and matrix metalloproteinase‐9 (MMP‐9) activation, an important step in the production of GNDF. However, the precise mechanism of MMP‐9 activation by antidepressants has yet to be identified, in particular the intracellular signaling pathway between LPAR1/Gαi/o and MMP‐9. Methods and Results Treatment of rat C6 astroglial cells (C6 cells) with amitriptyline increased Src family tyrosine kinase phosphorylation in a time and concentration‐dependent manner. Amitriptyline‐induced GDNF mRNA expression was blocked by Src family tyrosine kinase inhibitors. In addition, inhibiting Src family tyrosine kinase blocked amitriptyline‐induced zymographic MMP‐9 activation in C6 cells. The amitriptyline‐induced zymographic MMP‐9 activity was completely blocked by selective inhibition of Gαi/o protein and LPAR1. Furthermore, the amitriptyline‐induced Src family tyrosine kinase phosphorylation was blocked by LPAR1, but not MMP‐9 inhibition, indicating that Src family tyrosine kinase involvement is downstream of LPAR1. Conclusions The current findings suggest that the pharmacological effect of antidepressant such as amitriptyline is mediated through an intracellular signaling pathway via the LPAR1/Gαi/o/Src family tyrosine kinase, which leads to MMP‐9 activation and GDNF production.